Prestasi Kerja Pendidikan Tinggi (PT) Menurun Dalam Manajemen Kinerja Era Sars-Covid-19 - Khairiah Khairiah; Ade Riska Nur Astari; Eri Samsidar; Amar Solid Hidayat; Akhli Nur Mubiarto (Al-Khair Journal: Management Education, 2021)
Abstract: This study aims to describe the work performance of higher education (PT) in the SARS-Covid 19 era. The method used is a descriptive qualitative approach. The components that become benchmarks are the achievement of work performance and organizational goals such as learning in the Covid 19 era, and the application of e-performance through planning, organizing, controlling and monitoring. These four things are mentioned in the higher education management function, namely planning, organizing, actuating and controlling. E-performance is a web-based performance measurement information system, the e-performance application is the initial platform for global involvement in higher education performance management. Higher education work management can be seen from Webometrics as a database of international recognition on college index rankings. This article discusses the causes, impacts and consequences of decreased work performance in the SARS-Covid 19 era. Campus management in an effort to improve work performance through e-performance applications in guarding webometrics in the SARS-Covid-19 era. The results show that there has been a decline in work performance in the SARS-Covid 19 era.Therefore, it is recommended to improve the work performance of PT, so improve performance management in the PT environment in the SARS-Covid 19 era.Keywords: Management, Decreasing Performance Achievement, e-performance, SARS-Covid 19 Abstrak: Kajian tulisan ini bertujuan untuk mendeskripsikan prestasi kerja Pendidikan tinggi (PT) di era SARS-Covid 19. Adapun metode yang digunakan dengan pendekatan kualitatif deskripsi. Komponen yang menjadi tolak ukur adalah pencapaian prestasi kerja dan tujuan organisasi seperti pembelajaran di era Covid 19, dan aplikasi e-performance melalui perencanaan, pengorganisasian, pengendalian dan pengawasan. Empat hal tersebut disebutkan dalam fungsi manajemen Perguruan Tinggi yaitu planning, organizing, actuating dan controlling. E-permormance adalah system informasi pengukuran kinerja berbasis web, aplikasi e-peformance adalah wadah awal adanya keterlibatan dunia global dalam manajemen kinerja perguruan tinggi. Manajemen kerja perguruan tinggi dapat dilihat dari Webometrics sebagai database pengakuan Internasional pada ranking indek perguruan tinggi. Artikel ini membahas penyebab, dampak dan akibat menurunnya prestasi kerja pada era SARS-Covid 19. Manajemen kampus dalam upaya meningkatkan prestasi kerja melalui aplikasi e-performance dalam mengawal webometric di era SARS-Covid-19. Hasilnya menunjukkan bahwa telah terjadi penurunan prestasi kerja di era SARS-Covid 19. Oleh karena itu disarankan untuk meningkatkan prestasi kerja PT, maka tingkatkan manajemen kinerja di lingkungan PT pada era SARS-Covid 19.Kata Kunci: Manajemen, Prestasi Kinerja Menurun, e-performance, Era SARS-Covid 19